(untitled) (Asian Education Studies, 2022)
In February 2021, Xi Jinping, general Secretary of the Party history study education mobilization conference proposed "Publicity and education in the history of the Party, the history of the new China, the history of reform and opening up, and the history of the development of socialism should be widely carried out throughout society, Popularize the knowledge of Party history, promote the study and education of Party history to the masses, grassroots and popular, and make it clear that we should do a good job in the study and education of young people to carry on the red gene and revolutionary fire. At this point, the national colleges and universities set off the upsurge of learning "four history", focusing on strengthening the ideal and faith education of young students. Policy instruction and university implementation promote the good development of college students’ ideals and beliefs, but there are still many problems. Based on the realistic dilemma, we should make good use of the rich red resources contained in the "four Histories", dig deep into the theoretical depth, guide students to firm up the "four self-confidence", "fully understand" the historical mission of realizing the great rejuvenation of the Chinese nation, and establish correct ideals and beliefs.